Image Reconstruction: Applications in Medical Sciences - Zeng, Gengsheng Lawrence (De Gruyter Textbook, 2017)
This book introduces the classical and modern image reconstruction technologies.It covers topics in two-dimensional (2D) parallel-beam and fan-beam imaging, three-dimensional (3D) parallel ray, parallel plane, and cone-beam imaging.Both analytical and iterative methods are presented.